STUDIES ON THE EFFECT OF INTEGRATED NUTRIENT MANAGEMENT IN GEMENT IN GEMENT IN CYMBIDIUM GIGANTEUM UNDER SHEVAROYS CONDITION - A. SANKARI, M. ANAND; R. ARULMOZHIYAN, AND (The Bioscan, 2016)
An investigation was carried out during 2008 -2013 to study the effect of Integrated Nutrient Management in Cymbidium giganteum under Shevaroy condition. The results revealed that in Cymbidium giganteum,the treatment thus increased the plant height (65.7 cm) and number of leaves per plant (34.6 nos).Among the treatments maximum number of pseudobulbs per plant (4.4),maximumof Stalk length (96.6 cm), pedicel length (2.7 cm), floret size or flower diameter (2.0 cm), number of flowers per spike(14.8 Nos), number of spikes per plant(3.0 Nos), longevity of flowers in plants (31.3 days ) and the vase life in water (25.8 days) were recorded in treatment T 13.Thus it can be concluded from the findings that application of Common basal dose (N:P:K 30:10:10), FYM 1.0 Kg per pot + Decomposed Coir Compost 100g per pot + Biofertilizers (VAM + Azospirillum + Trichoderma viride 20g per pot) + 3% Panchakavya + 3% Manchurian tea can be recommended for Cymbidium giganteum under Shevaroy hill of Eastern Ghats.